OPTIMISING IVIG DELIVERY IN A TERTIARY NEUROLOGY CENTRE. Issue 12 (15th November 2016) - Zarkali, Angeliki; Bonifacio, Guendalina; Englezou, Christina; Parsons, Victoria Van Hamel; Renshaw, Hanna; Ingle, Gordon; Manji, Hadi; Reilly, Mary; Lunn, Michael; Carr, Aisling
Abstract : Objectives: Regular intravenous immunoglobulin (IVIg) is commonly used for autoimmune neurological conditions. In our hospital, 388 patients received 203, 571 grams of IVIg in 2014/15 amounting to 3127 patient-days. Given potential side effects, cost and impact to patients, we reconfigured our service to improve clinical assessment prior to IVIg administration and reduce waiting times. Methods: We mapped a typical patient journey and minimised processes that did not add value. Through workshops with juniors, consultants, nurses, managers and pharmacists we identified drivers for delays and suboptimal assessments, and raised awareness of the issue. Finally, we trialed a clerking proforma with prompts for risk factors and a junior doctor-led '2-Step IVIG clinic' for IVIg day admissions. Results: We audited 62 patients over 12 weeks. Following our interventions, mean waiting time from arrival to IVIg administration was reduced from 71.2 (median 55, IQR 5–160) to 20.7 minutes (median 20, IQR 5–30). Pre-IVIG clinical assessment was also improved with 100% of patients assessed for thromboembolism (from 45.5%), infection (from 90.9%) and comorbidities (from 72.7%). Conclusion: Our project highlights the importance of a multidisciplinary approach, allowing us to implement significant changes in the unit's structure, reduce unnecessary waiting times and ensure safe administration of IVIg.